Optimism during pregnancy and obstetrical outcomes: A systematic review. (May 2020) - Giangiordano, Ilaria; Sahani, Harshini; Di Mascio, Daniele; Saccone, Gabriele; Bellussi, Federica; Berghella, Andrea; Braverman, Andrea; Berghella, Vincenzo
Abstract: Objective: To ascertain the strength of association between dispositional optimism, assessed with the Revised Life Orientation Test (LOT-R), and obstetrical outcomes, and to evaluate women's social characteristics that may lead to low dispositional optimism during pregnancy. Study design: The research was conducted using MEDLINE, EMBASE, Scopus, Web of Sciences, Cochrane Database, and ClinicalTrial.gov as electronic databases. The articles were identified with the use of a combination of the relevant heading term, key words, and word variants for: "optimism" or "happiness" and "pregnancy" or "obstetrical outcomes", from the inception of each database to June 2019. Review of articles also included the abstracts of all references retrieved from the search. Randomized, cohort, case-control, or case series were all accepted study designs. Only studies reporting obstetrical outcomes in women undergone LOT-R to assess dispositional optimism during pregnancy were included. Obstetrical outcomes included preterm birth, pre-eclampsia and small for gestational age fetuses. All analyses were carried out using the random effects model. Dichotomous variables were analyzed using the odds ratio (OR) with a 95 % confidence interval (95 % CI). No continuous variables were compared in the analysis. Significance level was set at P < 0.05. Heterogeneity was measured using I-squared (Higgins I 2 ). Results: Two prospective cohort studies, including 3, 570 pregnancies undergone LOT-R - mostly during the second trimester - were included in the systematic review. Out of the 3, 570 pregnancies included, 411 were in the lowest quartile of optimism, according to LOT-R score. Dispositional optimism showed a trend towards lower incidence of preterm birth (7.6 % vs 9.7 %; OR 0.76, CI 0.53–1.09); no difference between women at higher levels and women in the lowest quartile of optimism was found in preeclampsia and small for gestational age. Women at higher levels of dispositional optimism were significantly associated with: age ≥ 30 years; marriage or "marriage-like status"; lower rates of public assistance and smoking; white ethnicity; higher rates of higher education. Conclusion: There are limited data on optimism and obstetric outcomes. Higher levels of optimism, evaluated by the LOT-R tool in two studies, are associated with a non-significant decrease in preterm birth.